Age-Related Exosomal and Endogenous Expression Patterns of miR-1, miR-133a, miR-133b, and miR-206 in Skeletal Muscles - Mytidou, Chrystalla; Koutsoulidou, Andrie; Zachariou, Margarita; Prokopi, Marianna; Kapnisis, Konstantinos; Spyrou, George M.; Anayiotos, Andreas; Phylactou, Leonidas A. (Frontiers in Physiology, 2021)
Skeletal muscle growth and maintenance depend on two tightly regulated processes, myogenesis and muscle regeneration. Both processes involve a series of crucial regulatory molecules including muscle-specific microRNAs, known as myomiRs. We recently showed that four myomiRs, miR-1, miR-133a, miR-133b, and miR-206, are encapsulated within muscle-derived exosomes and participate in local skeletal muscle communication. Although these four myomiRs have been extensively studied for their function in muscles, no information exists regarding their endogenous and exosomal levels across age. Here we aimed to identify any age-related changes in the endogenous and muscle-derived exosomal myomiR levels during acute skeletal muscle growth. The four endogenous and muscle-derived myomiRs were investigated in five skeletal muscles (extensor digitorum longus, soleus, tibialis anterior, gastrocnemius and quadriceps) of 2-week to 1-year-old wild-type male mice. The expression of miR-1, miR-133a, and miR-133b was found to increase rapidly until adolescence in all skeletal muscles, whereas during adulthood it remained relatively stable. By contrast, endogenous miR-206 levels were observed to decrease with age in all muscles, except for soleus. Differential expression of the four myomiRs is also inversely reflected on the production of two protein targets; serum response factor and connexin 43. Muscle-derived exosomal miR-1, miR-133a, and miR-133b levels were found to increase until the early adolescence, before reaching a plateau phase. Soleus was found to be the only skeletal muscle to release exosomes enriched in miR-206. In this study, we showed for the first time an in-depth longitudinal analysis of the endogenous and exosomal levels of the four myomiRs during skeletal muscle development. We showed that the endogenous expression and extracellular secretion of the four myomiRs are associated to the function and size of skeletal muscles as the mice age. Overall, our findings provide new insights for the myomiRs’ significant role in the first year of life in mice.